Social-Cultural Relationship with Stunting Incidence in Children Aged 24-59 Months - Selva, Petrorima; Krianto Karjoso, Tri (Indonesian Health Journal, 2023)
Stunting is a chronic condition of poor linear growth in children. The prevalence of stunting in Indonesia in 2018 reached 30.8%. With the complexity of the causes of stunting, one of the efforts being campaigned by the government is using local food. This study aimed to determine and analyze the influence of local food culture on preventing and overcoming stunting in toddlers (6-59 months) in Indonesia. The method used in this study is a systematic review based on the PRISMA guidelines. The results of this study show that a review of the seven selected journals shows that local food culture influences improving the nutritional status of toddlers, especially during the stunting prevention phase. Whereas in the prevention phase, local food culture by utilizing processed food forms has not improved the nutritional status of toddlers already suffering from stunting. Local food for toddlers who suffer from stunting must be accompanied by other supplements to have a significant effect. Food and eating in the community have cultural and social values, so the utilization of local food culture for toddler food will be easily accepted, easy to obtain, and affordable, significantly influencing stunting prevention in the regions. This research has implications for the importance of remembering that the results of this research can make a valuable contribution to the health and development of children in Indonesia and inspire concrete action to prevent funds from overcoming stunting.